Pitih Balanjo in Courtship: Minangkabau Traditions and their Compliance with Islamic Law - Ramadhani, Suci Isra; Dantes, Raymond (El-Rusyd, 2025)
This study examines the tradition of pitih balanjo, in which a prospective groom provides a monetary gift to his prospective bride during the courtship period in Minangkabau society, and evaluates its compliance with Islamic law. This tradition has long been an integral part of the social system and is regarded as a symbol of a man’s sincerity in proposing marriage. The value of pitih balanjo is determined not by the amount given but by the giver’s sincerity. The study employs a qualitative method with an ethnographic approach, including interviews, participant observation, and documentation, to gain an in-depth understanding of the practice and its socially constructed meanings. Findings indicate that the community views pitih balanjo as a symbolic bond between prospective partners, preventing others from proposing to the woman after the gift is given. However, the traditional sanction requiring the gift to be returned double in case of a canceled engagement contradicts the Islamic principle of voluntary gifts (hibah), which cannot be withdrawn except in specific contexts, such as by a father to his child. The study concludes that the giving of pitih balanjo is permissible as long as it complies with Sharia, while the traditional sanction mechanism warrants reconsideration.